Role of Corticotropin Releasing Factor in the Neuroimmune Mechanisms of Depression: Examination of Current Pharmaceutical and Herbal Therapies - Jiang, Yizhou; Peng, Tangming; Gaur, Uma; Silva, Marta; Little, Peter; Chen, Zhong; Qiu, Wei; Zhang, Yandong; Zheng, Wenhua (Frontiers in Cellular Neuroscience, 2019)
Approximately 3% of the world population suffers from depression, which is one of the most common form of mental disorder. Recent findings suggest that an interaction between the nervous system and immune system might be behind the pathophysiology of various neurological and psychiatric disorders, including depression. Neuropeptides have been shown to play a major role in mediating response to stress and inducing immune activation or suppression. Corticotropin releasing factor (CRF) is a major regulator of the hypothalamic pituitary adrenal (HPA) axis response. CRF is a stress-related neuropeptide whose dysregulation has been associated with depression. In this review, we summarized the role of CRF in the neuroimmune mechanisms of depression, and the potential therapeutic effects of Chinese herbal medicines as well as other agents. Studying the network of CRF and immune responses will help to enhance our understanding of the pathogenesis of depression. Additionally, targeting this important network may aid in developing novel treatments for this debilitating psychiatric disorder.